2000
DOI: 10.1016/s0304-4149(00)00037-5
|View full text |Cite
|
Sign up to set email alerts
|

Convergence to the maximal invariant measure for a zero-range process with random rates

Abstract: We consider a one-dimensional totally asymmetric nearest-neighbor zero-range process with site-dependent jump-rates -an environment. For each environment p we prove that the set of all invariant measures is the convex hull of a set of product measures with geometric marginals. As a consequence we show that for environments p satisfying certain asymptotic property, there are no invariant measures concentrating on configurations with density bigger than ρ * (p), a critical value. If ρ * (p) is finite we say that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(66 citation statements)
references
References 13 publications
2
64
0
Order By: Relevance
“…These measures are invariant for the process [1,13,22]. In some cases it is known that all invariant measures (concentrated on X ) are convex combinations of measures in {ν λ,v : 0 ≤ v ≤ c} (see [1,2]). …”
Section: Resultsmentioning
confidence: 99%
“…These measures are invariant for the process [1,13,22]. In some cases it is known that all invariant measures (concentrated on X ) are convex combinations of measures in {ν λ,v : 0 ≤ v ≤ c} (see [1,2]). …”
Section: Resultsmentioning
confidence: 99%
“…The purpose of this paper is to introduce a new approach for the derivation of quenched strong local equilibrium in order to address this question, which was left open by the previous works [10,21]. In the case of supercritical hydrodynamic density ρ(t, x) > ρ c , we prove that the local equilibrium property fails, and that, locally around "typical points" of the environment, the distribution of the microscopic state is close to the critical measure with density ρ c : this can be viewed as a dynamic version of the loss of mass property studied in [4,7,8]. The dynamic loss of mass that we establish here allows us to remove the convexity assumption used in [7,8], but for a slightly less general class of initial configurations.…”
Section: Introductionmentioning
confidence: 75%
“…This corresponds to a critical density above which no product invariant measure exists. More generally, [4] showed that there were no invariant measures (whether product or not) of supercritical density, which can be interpreted as a phase transition. The model of M/M/1 queues in tandem has specific properties which make its analysis more tractable than that of the general model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…≡ 1 and p(.) concentrated on the value 1, we obtain M/M/1 queues in tandem, for which [2] showed that there were no invariant measures of supercritical density.…”
Section: Introductionmentioning
confidence: 93%